Onset and duration of epidural analgesia with bupivacaine and bupivacaine plus fentanyl: a comparative study - Umapathy, Pujala; Ayathullah, Md. (International Journal of Research in Medical Sciences, 2017)
Background: Bupivacaine has got the more cardiac toxicity due to high degree of protein binding. There have been many attempts for improving the duration and onset of epidural block. Fentanyl when administered epidurally was found to reduce the requirement of doses by double in some cases. The objective of the study was to compare the efficacy of bupivacaine plus fentanyl in terms of onset and duration of epidural analgesia. Methods: A clinical study was undertaken to evaluate the onset and duration of analgesia with bupivacaine and mixture of bupivacaine plus fentanyl when given epidurally for patients undergoing lower limb orthopedic surgeries. The study was undertaken in 50 patients who were divided into two groups of 25 each. The patients were undergoing surgery in orthopedic theatre at S. V. S. Medical College and Hospital. Patients studied comprised of both the sexes between the 18-55 years of age. Results: It is seen that the onset of analgesia was equal in both the groups 72% of patients in group II had excellent quality of intra operative analgesia compared to only 36% of patients in group I. This difference was found to be statistically significant (p<0.05). It was seen that none of the patients had analgesia of less than 1 hour 30 minutes. The two-segment regression time was uniformly distributed amongst the two groups. It was found that the incidence of intra operative complications like bradycardia, hypotension, nausea/vomiting were almost equal in both the groups. It was found that the duration of post-operative analgesia in patients of two groups was almost equal. Conclusions: Addition of fentanyl to bupivacaine was found to increase the quality of intra operative analgesia. Otherwise there was no added advantage over bupivacaine alone.